2021
DOI: 10.1017/jog.2021.47
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sensor remote sensing to map glacier debris cover in the Greater Caucasus, Georgia

Abstract: Global warming is causing glaciers in the Caucasus Mountains and around the world to lose mass at an accelerated pace. As a result of this rapid retreat, significant parts of the glacierized surface area can be covered with debris deposits, often making them indistinguishable from the surrounding land surface by optical remote-sensing systems. Here, we present the DebCovG-carto toolbox to delineate debris-covered and debris-free glacier surfaces from non-glacierized regions. The algorithm uses synthetic apertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Paul and others (2015) have reported that errors involved in mapping glaciers can be significant when glaciers are heavily debris-covered and that this is a major challenge for glaciological studies (Shukla and others, 2010; Paul and others, 2015). The complex physical characteristics of debris-covered ice make it difficult to map with optical remote sensing (Holobâcă and others, 2021). Most studies are limited to small geographical regions and where only a small number of glaciers (<5) are analyzed (Robson and others, 2015; Kaushik and others, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Paul and others (2015) have reported that errors involved in mapping glaciers can be significant when glaciers are heavily debris-covered and that this is a major challenge for glaciological studies (Shukla and others, 2010; Paul and others, 2015). The complex physical characteristics of debris-covered ice make it difficult to map with optical remote sensing (Holobâcă and others, 2021). Most studies are limited to small geographical regions and where only a small number of glaciers (<5) are analyzed (Robson and others, 2015; Kaushik and others, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Given that manual glacier delineation is problematic for debris cover and/or snowfields [42], many fully automatic methods have emerged [43]. Additionally, the comprehensive multi-platform datasets of SAR coherence images were also combined and applied with visible, thermal spectrums and DEM [44].…”
Section: Glacier Delineationsmentioning
confidence: 99%
“…The delineation process is challenging for debris-covered glaciers. Various studies have focused on the automatic delineation of debris-covered glaciers (Bhardwaj et al, 2014;Holobâcă et al, 2021;Mölg et al, 2018). In the present study, all the glaciers with an area > 0.5 km 2 have been studied, which include both clean-ice and debris-covered glaciers.…”
Section: Glacier Delineationmentioning
confidence: 99%